1992
DOI: 10.3109/00498259209053145
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of oxybutynin and its N-desethyl metabolite in plasma, and its application to pharmacokinetic studies in young, elderly and frail elderly volunteers

Abstract: 1. A quantitative h.p.l.c. plasma assay for oxybutynin (OB) and its active metabolite, N-desethyl oxybutynin (DEOB) is described. The method is linear with coefficients of variation ranging between 4 and 11.8% for OB and 4.6-9.1% for DEOB over the typical concentration range measured. Minimum detectable levels were 0.5 and 5 ng/ml for OB and DEOB respectively from a 2 ml sample. 2. Pharmacokinetic parameters were obtained after a single oral dose of OB and after administration two or three times daily to frail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0
6

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(85 citation statements)
references
References 13 publications
2
77
0
6
Order By: Relevance
“…In the human pharmacokinetic volunteer study, we found that the serum level of DEOB was higher than that of oxybutynin in case of oral administration (data not shown). Hughes et al (32) reported that high levels of orally administered oxybutynin were matched by high DEOB metabolite levels in young, elderly and frail elderly volunteers. Moreover, Saitoh et al (33) also reported that plasma levels of oxybutynin were almost equal to those of DEOB even in the instillation of intravesical oxybutynin in overactive bladder patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the human pharmacokinetic volunteer study, we found that the serum level of DEOB was higher than that of oxybutynin in case of oral administration (data not shown). Hughes et al (32) reported that high levels of orally administered oxybutynin were matched by high DEOB metabolite levels in young, elderly and frail elderly volunteers. Moreover, Saitoh et al (33) also reported that plasma levels of oxybutynin were almost equal to those of DEOB even in the instillation of intravesical oxybutynin in overactive bladder patients.…”
Section: Discussionmentioning
confidence: 99%
“…C'est une amine tertiaire qui a pour métabolite actif la N-déséthyloxybutynine [25][26][27] . Stohrer a signalé une amélioration de la capacité vésicale de 164 ml à 298 ml, avec diminution de la pression détrusorienne maximale de 68,6 cm H 2 O à 43 cm H 2 O chez des patients présentant une hyperactivité détrusorienne 28 .…”
Section: Chlorhydrate D'oxybutynineunclassified
“…Stohrer a signalé une amélioration de la capacité vésicale de 164 ml à 298 ml, avec diminution de la pression détrusorienne maximale de 68,6 cm H 2 O à 43 cm H 2 O chez des patients présentant une hyperactivité détrusorienne 28 . D'autres formules d'oxybutynine permettent de limiter les effets secondaires ; c'est notamment le cas de la formule à libération prolongée (prise quotidienne), du timbre cutané, du gel topique, du suppositoire et du médicament en instillation intravésicale [25][26][27] . L'essai aléatoire à double insu OPERA a permis d'étudier, pendant 12 semaines, l'efficacité de l'oxybutynine à libération prolongée (10 mg) auprès de 790 femmes.…”
Section: Chlorhydrate D'oxybutynineunclassified
“…It is known that orally administered oxybutynin is rapidly absorbed from the gastrointestinal tract with the major pathway of elimination by hepatic metabolism (28) and that the plasma concentration of DEOB in humans after oral administration is much higher than that of oxybutynin (29). Based on previous reports that muscarinic receptor binding affinity of DEOB was greater in the salivary gland than in the bladder (30,31), it is considered that DEOB may be responsible for the longlasting occupation of exocrine muscarinic receptors after oral oxybutynin.…”
Section: Transdermal Oxybutyninmentioning
confidence: 99%